Studies on Al-Cu-Fe Quasicrystalline and 6082 Al-alloy based Metal Matrix Composites - Shadangi, Yagnesh (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Studies on Al-Cu-Fe; Quasicrystalline and 6082 Al; alloy based Metal Matrix Composites